Political Cadre Structure and National Purpose in Nepal - Karki, Pralhad (NPRC Journal of Multidisciplinary Research, 2025)
Political parties in Nepal have broadened their organizational space by linking cadres operating in schools, colleges, and universities, as well as unions, professional organizations, and government structures. While once associated with democratization and representation, their overuse has eroded public confidence and weakened legitimacy. This study adopts a review-based methodology, synthesizing academic literature, policy documents, media reports, and survey data using thematic analysis. Findings show cadres are indispensable to parties but corrosive to institutions, creating a paradox where numerical strength coexists with declining trust. The judiciary, education, and professional bodies reveal deep politicization. The paradox undermines Nepal’s national purpose by weakening fairness, equity, transparency, and trust. This article integrates political theory (Weber, Freire, Sen, Rawls, Dewey) with Nepal’s cadre politics and highlights justice-sector capture as a central challenge to national purpose. This pattern is evident in judicial reform efforts, where party cadres often undermine constitutional checks on power (Chapagain, & Karna,, 2004,). Even in school governance, cadres dominate local management committees, crowding out community participation.